Characteristics Shared between Lung Development and Tumorigenesis: Mini Review Article (Global Journal of Medical Research, 2021)
Cells with characteristics of embryonic stem cells, and cancer stem cells are at the basis of both embryo development and the cancer process. At the same time, they share signaling pathways, such as the hedgehog, Notch, Wnt, TGF beta, among others. This knowledge is important for understanding the pulmonary regeneration process and for the development of new target therapies.
Keywords: embryogenesis; alveolarization; lung; tumorigenesis; molecular biology; signaling pathways